Travessias pela cultura africana e afro-brasileira em Amoras e O mundo no black power de Tayó: uma experiência de leitura literária com alunos do 5º ano do ensino fundamental I em Massaranduba-PB - Silva, Jahelina de Almeida (2024)
In the first phase of elementary school, literary reading is a discontinuous and unsystematic practice. Literary works are often used as a pretext for teaching metalinguistic and/or moral content. In addition to this, we also note the absence of work with texts written by and/or with Afro-Brazilian themes. Therefore, considering the importance of school in the training of readers, especially in third childhood, and being aware of the relevance of contact with texts that allow the discussion of ethnicracial issues in the training of students, this research seeks to answer the following question: how can Afro-Brazilian children's literature guide conversations/dialogues about ethnic-racial relations and African and Afro-Brazilian culture in elementary school? Will there be identification between texts and readers? Will contact with these texts lead students to reflect on being a child and being black in our society? To what extent will students' horizons be broadened by reading and reflecting on the work Amoras, by Emicida (2018), and O mundo no black de Tayó, by Kiusam de Oliveira (2013) in comparison to other texts belonging to genres distinct, but with a similar theme to these two works? Therefore, our general objective was to observe and analyze the reception of these works by students in the fifth year of elementary school. As specific objectives, we outline: 1) problematize aspects of Afro-Brazilian culture based on Law 10.639/03 and the inclusion of Afro-Brazilian children's literature in the Elementary School I classroom; 2) develop a didactic sequence with didactic-methodological procedures that guide work in the classroom with the selected corpus. To support our research proposal, regarding the training of readers and the teaching of literature, we are based on the Aesthetics of Reception and Theory of Effect from the perspective of Jauss (1979), in the proposal for a reception method in accordance with Aguiar and Bordini (1988) and in the assumptions of literary literacy according to Cosson (2006) and Teresa Colomer (2007). With regard to ethnic-racial issues, we are based on Gomes (2007), Munanga (2005), Zin (2022), Pinheiro (2023), Ribeiro (2019) in addition to the guidelines present in documents such as the Common National Base Curricular (BNCC) and the National Curricular Guidelines for the Education of Ethnic-Racial Relations and for the Teaching of Afro- Brazilian and African History and Culture. Methodologically, our scientific research proposal is part of the list of ethnographic research in the area of Education and is classified as qualitative, exploratory and also applied. As instruments for data collection, we used the research diary, printed questionnaire or Google Forms, in addition to unstructured observation.